Effects of Increasing Soybean Meal in Corn-Wheat Midds-Based Diets on Growth Performance and Carcass Characteristics of Late Finishing Pigs - Julia P. Holen; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Chad W. Hastad; Zach B. Post (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 786 pigs (PIC TR4 × (Fast LW × PIC L02); initially 213.2 lb ± 2.37 lb) were used to evaluate the effects of increasing soybean meal (SBM) in corn-wheat middsbased diets on growth performance of late finishing pigs. Pens of pigs were blocked by BW and randomly assigned to 1 of 5 treatments with 9 replications per treatment. Experimental diets were corn-based with 30% wheat midds. Soybean meal levels increased from 0 to 16% replacing added feed grade AA. Pens of pigs were weighed to evaluate ADG, ADFI, and F/G. Data were analyzed with the GLIMMIX procedure of SAS and pen was considered as the experimental unit. The statistical model considered fixed effects of dietary treatment, linear, quadratic, and cubic contrasts, and random effects of block. Overall, final BW of pigs increased (linear,P<0.05) as dietary SBM increased. Additionally, overall ADG and F/G improved as SBM increased (linear and cubic;P<0.05) with no differences in overall ADFI. Although diets were formulated to exceed minimum NRC nutrient requirement estimates, we suspect that the increased Trp:Lys ratio in the 16% SBM diet may explain the cubic responses observed. These results suggest that corn-soybean meal-based diets with 30% wheat midds for late finishing pigs should contain at least 4% SBM.
Keywords: amino acids; crude protein; finishing pigs; soybean meal; wheat midds